Intestinal Perforation during the Stabilization Period in a Preterm Infant with Congenital Diaphragmatic Hernia - Straňák, Zbyněk; Pýcha, Karel; Feyereislova, Simona; Feyereisl, Jaroslav; Rygl, Michal (European journal of pediatric surgery reports, 2017)
Background Delayed surgery after stabilization of infants with congenital diaphragmatic hernia (CDH) is an accepted strategy. However, the evidence favoring delayed versus immediate surgical repair is limited. We present an extremely rare case of a very low-birth-weight infant with prenatally diagnosed left-sided CDH and unexpected transmural bowel perforations developing within the postnatal stabilization period. Case Report A neonate born at 31st week of gestation with a birth weight of 1,470 g with antenatally diagnosed left-sided CDH presented with bowel dilation leading to transmural bowel perforations on the 2nd day of life. Meconium pleuroperitonitis resulted in severe systemic inflammatory response syndrome, pulmonary hypertension, multiple organ failure, and death. Conclusion In neonates with CDH deteriorating under standard postnatal management, intestinal perforation, and early surgical intervention should be considered.
Keywords: bowel perforation; congenital diaphragmatic hernia; delayed surgery